Real-world evidence for carfilzomib dosing intensity on overall survival and treatment progression in multiple myeloma patients. (July 2022) - Raje, Noopur; Medhekar, Rohan; Panjabi, Sumeet; Hines, Dionne M; Wang, Xin; Iskander, Karim; Welliver, Tim; Wade, Rolin L; Ailawadhi, Sikander
Introduction: Carfilzomib dosing as a single agent or in combination with dexamethasone (Kd) has evolved from the initial 27 mg/m 2 twice-weekly (legacy dose), to more recently approved doses of 56 mg/m 2 twice-weekly and 70 mg/m 2 once-weekly (optimized doses). The objective of this study was to evaluate the overall survival (OS), and time to next treatment (TTNT) among multiple myeloma patients treated with Kd optimized vs legacy doses. Methods: A retrospective analysis of patients receiving Kd between 01/01/2013–07/31/2017 was conducted using IQVIA's oncology electronic medical records database. Kd dose was estimated based on body surface area. OS was measured from the Kd-initiation date until death. TTNT was defined as the time from Kd-initiation until the start of subsequent treatment. Kaplan-Meier analysis and Cox models were used to evaluate OS and TTNT. Results: Of the 1, 469 patients evaluated, 129 (8.8%) received optimized dose and 1, 340 (91.2%) received legacy dose. Risk of mortality was 64% lower for patients receiving the optimized doses (HR: 0.36, 95% CI: 0.178–0.745). Patients receiving the optimized doses had significantly longer TTNT compared to patients receiving the legacy dose (median TTNT: 17.5 months [95% CI: 14.8-NE] and 13.2 months, [95% CI: 12.4–14.4], respectively; p = 0.023), and 33% lower risk of progressing to the subsequent treatment (HR: 0.67, 95% CI: 0.48–0.93). Conclusions: Patient outcomes could be improved if eligible MM patients are treated with the optimized, recently approved Kd doses (56 mg/m 2 twice-weekly and 70 mg/m 2 once-weekly).